Broncho‐gastric fistula complicating mechanical ventilation. Issue 2 (6th December 2016) - Atladottir, Hjördis Osk; Kim Schønemann, Niels
Summary: A broncho‐gastric fistula is a communication between a bronchus and the stomach and is an extremely rare complication following an oesophagectomy. A patient was admitted to the intensive care unit with acute respiratory distress. He had previously undergone a gastric pull‐up and received radiotherapy for oesophageal cancer. Because of a previously undiagnosed broncho‐gastric fistula, there was considerable air leakage during mechanical ventilation that resulted in repeated tracheal intubations during an acute phase, in an unstable patient. To the best of our knowledge, there are no previous reports of a fistula appearing so many years after the original surgery. We emphasize the need to consider the possibility of late complications in patients that have received surgery and/or radiation therapy to the thoracic area.